The Effect of Sport on Tolerance Level of Secondary School Students against Themselves - AKANDERE, Mehibe; ÇELİK, Ayşegül and ALTIN, Mehmet and BAŞTUĞ, Gülsüm (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2015)
The study was made with the aim of determining the effect of sport on tolerance level of secondary school students against themselves. A total of 400 students from the schools in city centre of Konya, of whom 200 do sports (100 boys and 100 girls) and 200 who don’t (100 boys and 100 girls) voluntarily participated in the study. Tolerant scale that was developed by Ersanlı in 2004, consisted of 30 items, was used to determine the participants’ tolerance level. In the evaluation of the obtained data SPSS for Windows 16 was used. After evaluating normal dispersion of the data and the homogeneous of the variances independent samples t test and One Way Anova were used to determine the significant differences and also in the differences between groups Tukey test was used. While no difference was observed in tolerance level against themselves of male secondary school students who do sport or not, significant difference was observed in the tolerance level of female students who do sport compared to female students who do not (p<0.05). When all groups were considered there was a significant difference in the tolerance level against themselves of students who do sport compared to students who do not (p<0.05). There were no significant differences according to mother and father education status, age, level of income, number of sisters/brothers, there was a significant difference according to education class (p<0.05). According to study findings it can be said that students who do sports actively are more tolerant to theirselves and to their environments than the students who don’t do sports and the girl students who do sports are more tolerant to themselves and to their environments than the girl or boy students who don’t do sports.